PENGEMBANGAN BAWANG SABRANG (Eleutherin americana Merr) PADA MEDIA GAMBUT DENGAN PENGGUNAAN BIOFERTILIZER DAN PUPUK KALIUM - Sinaga, Dewi Betharia; Zulfita, Dwi; Surachman, Surachman (Jurnal Sains Pertanian Equator, 2025)
Sabrang onion is an endemic plant of Central Kalimantan traditionally used by the Dayak people as a medicinal plant. However, its growth in peat soil is often suboptimal due to low availability of macronutrients such as P, K, Ca, and Mg, as well as micronutrients including Cu, Zn, Fe, and Mn. Improving nutrient availability can be achieved through the application of biofertilizer and potassium fertilizer. This study aimed to determine the best interaction between biofertilizer and K fertilizer doses on the growth and yield of sabrang onion grown in peat soil. The experiment used a factorial Completely Randomized Design with two factors: biofertilizer (2.5, 5, and 7.5 tons/ha, equivalent to 9, 18, and 27 g/plant) and KCl fertilizer (40, 60, and 80 kg/ha, equivalent to 0.16, 0.22, and 0.30 g/plant). Nine treatment combinations were replicated three times, resulting in 81 experimental plants. Observed variables included root volume, number of tillers per clump, plant height, number of leaves, number and weight of fresh tubers per clump. The results showed that biofertilizer at 2.5 tons/ha combined with KCl at 40 kg/ha produced the best growth and yield of sabrang onion in peat soil.